2019
DOI: 10.1007/s00784-019-02957-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating unset endodontic sealers’ eugenol and hydrocortisone roles in modulating the initial steps of inflammation

Abstract: Introduction. Endodontic treatment success is achieved not only when the cement provides a hermetic seal but also when the injured periapical tissue is regenerated. However, an exaggerated inflammatory reaction hinders tissue regeneration and it has been shown that dental materials affect the inflammatory response through modulation of cytokine secretion. This work was set to investigate a hydrocortisone-containing sealer (Endomethasone N) modulatory effects on the initial steps of inflammation in vitro. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
7
0
2
Order By: Relevance
“…LPS of bacteria in carious lesions stimulate TLRmediated responses, which lead to activation of the proinflammatory The burst release of TNF-α cytokine as a major inflammatory mediator from activated monocytes/macrophages accumulates neutrophils and monocytes in the inflamed tissues. [37] This factor plays a key role in stimulating the inflammatory cascade and activates other cytokines such as IL-1β, IL-6, and IL-8 and growth factors. It has been shown that after bacterial infiltration, this cytokine is synthesized and released by a multitude of cell types and there are well-known correlations between TNF-α levels in the infected pulp tissue and experienced pain by patients.…”
Section: Discussionmentioning
confidence: 99%
“…LPS of bacteria in carious lesions stimulate TLRmediated responses, which lead to activation of the proinflammatory The burst release of TNF-α cytokine as a major inflammatory mediator from activated monocytes/macrophages accumulates neutrophils and monocytes in the inflamed tissues. [37] This factor plays a key role in stimulating the inflammatory cascade and activates other cytokines such as IL-1β, IL-6, and IL-8 and growth factors. It has been shown that after bacterial infiltration, this cytokine is synthesized and released by a multitude of cell types and there are well-known correlations between TNF-α levels in the infected pulp tissue and experienced pain by patients.…”
Section: Discussionmentioning
confidence: 99%
“…The major finding in the present study was that all dental adhesives modified inflammatory patterns. Contact with dental materials can, in fact, cause an inflammatory response [43,44] with over-production of inflammatory markers such as IL6, IL-8 [45,46], IL1β, IL-18 [47][48][49], all of which play major roles gingivitis and periodontal destruction [50,51]. Present observations showed all adhesives were associated with increased IL6 and IL8 expression after short-term exposure which dropped sharply at 48 h and increased IL1β at 48 h. We hypothesize this was due to their secretion in the extracellular compartment which might be an interesting starting point for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Kyung et al found that only bioceramic-based sealer Endosequence BC created smaller diameter of around 18 mm, while others (AH-Plus, AD Seal, Radic-Sealer, EndoSeal MTA, MTA Fillapex, AD Seal i Radic-Sealer) showed satisfying diameters (more than 20 mm) [31]. Jeanneau C et al investigated anti-inflammatory effect of Endomethasone N and Pulp Canal Sealer and found that only standard or thick consistency (adequate saturation of powder with eugenol) had effect on lessening the secretion of interleukine-6 [32].…”
Section: Discussionmentioning
confidence: 99%
“…Jeanneau C. i sar. ispituju antiinflamatorno dejstvo Endometazona N i silera Pulp Canal i zaključuju da samo standardno zamešan (ili kao gušća konzistencija) ovaj siler omogućava pravilno očvršćavanje i zasićenje cink-oksida eugenolom i na taj način ispoljava i svoje antiinflamatorno dejstvo smanjenjem lučenja interleukina-6 [32].…”
Section: Diskusijaunclassified